Direct graphene growth on (111) Cu2O templates with atomic Cu surface layer. (December 2015) - Liu, Jianwei; Liu, Qingfeng; Baca, Javier; Xu, Guowei; Rochford, Caitlin; Lu, Rongtao; Edwards, Christina M.; Berrie, Cindy L.; Maroni, Victor A.; Wu, Judy
Abstract: This work explores nucleation and epitaxy of graphene on crystalline Cu2 O templates formed via self-assembly and surface reduction of Cu2 O nanocrystallites on the cubic textured (100) orientation Cu (CTO-Cu) and polycrystalline Cu (poly-Cu) substrates, respectively. It has been found that the presence of sub-surface oxygen causes the reconstruction of Cu surface due to the formation of oriented Cu2 O nanocrystallites at a low H2 gas flow. Self-assembly of the Cu2 O nanocrystallites into a textured surface template provides direct nucleation sites for graphene growth after the oxygen-sublattice on the template surface is reduced. The atomic Cu surface layer provides advantages of high graphene growth rate due to the catalytic role of Cu and in-plane alignment of graphene nuclei. It is particularly important that the Cu2 O crystallites have predominantly (111) orientation aligned to each other in the plane of the (100) CTO-Cu substrates, which allows epitaxy of graphene with much lower defect density as compared to that in the poly-Cu case. Since Cu2 O (111) templates may be developed on lattice matched (100) surfaces of other dielectric materials, this self-assembly approach provides a promising pathway for large-scale, transfer free graphene epitaxy on nonmetallic surfaces.